2017
DOI: 10.1007/s11019-017-9819-5
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking moral distress: conceptual demands for a troubling phenomenon affecting health care professionals

Abstract: Recent medical and bioethics literature shows a growing concern for practitioners' emotional experience and the ethical environment in the workplace. Moral distress, in particular, is often said to result from the difficult decisions made and the troubling situations regularly encountered in health care contexts. It has been identified as a leading cause of professional dissatisfaction and burnout, which, in turn, contribute to inadequate attention and increased pain for patients. Given the natural desire to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 34 publications
0
30
0
Order By: Relevance
“…Even with infinite resources, clinicians would still need to ask whether it is ethically permissible to provide or continue LST and balance this with quality of life considerations. As some scholars have suggested, MD in these situations could be considered a natural response to morally troubling situations [23, 45, 69], and no amount of resources could mitigate the nature of these decisions. This is not to say we should ignore the MD that occurs due to unavoidable ethical challenges but rather that avoidable and unavoidable ethical challenges require different responses.…”
Section: Introductionmentioning
confidence: 99%
“…Even with infinite resources, clinicians would still need to ask whether it is ethically permissible to provide or continue LST and balance this with quality of life considerations. As some scholars have suggested, MD in these situations could be considered a natural response to morally troubling situations [23, 45, 69], and no amount of resources could mitigate the nature of these decisions. This is not to say we should ignore the MD that occurs due to unavoidable ethical challenges but rather that avoidable and unavoidable ethical challenges require different responses.…”
Section: Introductionmentioning
confidence: 99%
“…Arguably, only once the conceptual fog has cleared can healthcare professionals, researchers and policy‐makers can begin to gain further clarity regarding what, if anything, can be done to mitigate MD? Indeed, it has been suggested that MD is simply a natural response to morally troubling experiences that should be welcomed and that getting rid of MD is not only impossible but undesirable (personal communication with Tigard; hinted at in Tigard () and Howe ()). MD may be a natural consequence of the messiness of moral life but when one experiences MD everyday due to their occupation, which seems to be the case for nurses and other healthcare professionals, then it may instead be regarded as an occupational hazard that employers have a responsibility to address.…”
mentioning
confidence: 99%
“…However, recent studies have shown that the degree of moral competence development in all students is not equal and satisfactory (13,14). Moral behavior is the capacity to distinguish between right and wrong and to act accordingly (15). Nurses needs to reach to high levels of moral competence because most of the procedures and decisions in their daily practice have moral dimensions.…”
Section: Introductionmentioning
confidence: 99%